Barriers, facilitators and motivators of electronic community health information system use among health workers in Ethiopia - Tariku Nigatu Bogale; Selamawit Meressa Teklehaimanot; Tilahun Fufa Debela; Daniel Berhanie Enyew; Abebe Nigusse Bedada; Segni Dufera Kebebew; Adane Nigusie Weldeab; Dawit Wolde Daka; Herman Jozef Willems; Tadesse Alemu Bekele (Frontiers Media S.A., 2023)
BackgroundThe electronic community health information system (eCHIS) has been implemented in Ethiopia to support health services delivered by community health workers. Despite the many benefits of digitizing community health information systems, the implementation of the eCHIS is challenged by many barriers resulting in low uptake. This study assessed the barriers, facilitators, and motivators of eCHIS use among health workers with focus on health extension workers (HEWs) in Ethiopia.MethodsPhenomenological approach was used to assess the barriers, facilitators and motivators of eCHIS use in Amhara, Harari, Oromia, Sidama, South West Ethiopia and Southern Nation Nationalities and People's regions of Ethiopia. Data were collected from 15-29 May 2022. A total of 54 face-to-face in-depth interviews were conducted among HEWs, HEW supervisors, health information technicians and managers. The interviews were audiotaped using Open Data Kit, transcribed verbatim and translated into English. OpenCode 4.03 software was used for coding and categorizing the data. Thematic analysis was used to analyze the data.ResultsThe HEWs and other eCHIS users reported lack of infrastructure and resources; poor quality of training, follow-up, and supervision; parallel recording using the manual and electronic system; and HEWs' workload as barriers hindering eCHIS use. Data quality, retrievability, and traceability; tablet portability; encouragement from supervisors; and positive image in the community resulting from HEWs using tablets in their routine activities were the main facilitators of eCHIS use.ConclusionThe study identified various barriers that adversely affect the use of eCHIS. An integrated and coordinated approach to eCHIS implementation that encompasses removing the barriers, and reinforcing facilitators is required.